Effect of spermidine on uptake of chloroquine by Plasmodium berghei - Chang Hui-Ling; Wang Qin-Mei; Lan Qin-Xian; Qiu Chi-Ping (Acta Pharmacologica Sinica, 2016)
To probe into the effect of spermidine on chloroquine (Chl) uptake by P berghei and its role of Chl-resistance, mice infected with Chl sensitive strain (CS) of P berghei were given Chl 20 mg.kg-1 ig combined with spermidine (Spe) 42 mg.kg-1 ip. It was found that 3 and 16 h after combined administration, Chl quantity uptaken by the parasites was reduced respectively by 59.6% and 53.8% in comparison with that in the Chl group. However, there was no difference in parasitaemia between Chl group (2.3 +/- 1.0) and Chl-Spe group (1.7 +/- 1.0), whereas the untreated control group remained a parasitaemia of 36 +/- 9. The authors deemed that Chl resistance is not merely attributed to the insufficient quantity of Chl in the Chl resistant parasites, the change in the sensitivity to Chl of Chl resistant parasites and the role of Spe in Chl resistance production should also be taken into consideration.